2018
DOI: 10.1111/ijpo.12458
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of an early childhood obesity prevention program in a low‐income community: a pilot, randomized trial

Abstract: A multi-component behavioural intervention increased breastfeeding duration and decreased nocturnal awakenings in infants of low-income families.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
37
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(38 citation statements)
references
References 25 publications
(45 reference statements)
0
37
0
1
Order By: Relevance
“…Food frequency questionnaires (FFQs, n = 8 articles) 33–38,41,45 and 24‐h dietary recalls ( n = 6 articles) 29,31,32,40,43,44 were the most commonly used methods (Tables 3 and S3). In most cases, mothers who were aware of their group assignment reported infant dietary intake 29–41,43–45 . In terms of analysis, some studies analysed intake as a continuous variable, for example, grams per day, 29,33,40–42,44,45 while some considered it as a dichotomous variable, for example, whether the child ever consumed a particular food or drink 30–32,34–40,43,44 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Food frequency questionnaires (FFQs, n = 8 articles) 33–38,41,45 and 24‐h dietary recalls ( n = 6 articles) 29,31,32,40,43,44 were the most commonly used methods (Tables 3 and S3). In most cases, mothers who were aware of their group assignment reported infant dietary intake 29–41,43–45 . In terms of analysis, some studies analysed intake as a continuous variable, for example, grams per day, 29,33,40–42,44,45 while some considered it as a dichotomous variable, for example, whether the child ever consumed a particular food or drink 30–32,34–40,43,44 .…”
Section: Resultsmentioning
confidence: 99%
“…In most cases, mothers who were aware of their group assignment reported infant dietary intake 29–41,43–45 . In terms of analysis, some studies analysed intake as a continuous variable, for example, grams per day, 29,33,40–42,44,45 while some considered it as a dichotomous variable, for example, whether the child ever consumed a particular food or drink 30–32,34–40,43,44 . Most studies grouped foods together to create variables such as ‘savoury snacks’, 29‐33,35‐43 while some also considered intake of considered intake of specific food items such as bananas or water 31‐33,36,37,40,42,45 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Three articles examined prevention programmes among special populations. In the community setting and among low‐income populations, Cloutier and colleagues found that a multi‐component behavioural intervention was effective in improving two out of six obesity‐associated behaviours (increasing breastfeeding duration and decreasing nocturnal awakenings in infants). Hull and colleagues assessed the efficacy of a family‐based weight gain prevention intervention for Hispanic immigrant families; their results were impacted by low class attendance rates and they encouraged adopting strategies to maximize intervention engagement for this population.…”
mentioning
confidence: 99%